Inclusive Education From The Perspective of The Quran in Building Social Equality: A Literature Review - Chusyairi, Kholil; Mujahid, Mujahid; Muqowin, Muqowin (Universitas Islam Sultan Agung, 2025)
In some cases, children with special needs are still considered a burden and a shame by society because of a culture of negative thinking that has been passed down through generations. As a result, their opportunities for socialization and education are very limited. This condition can certainly trigger social injustice and inequality behavior, which can have a negative impact on the psychological development of children with special needs. One solution to overcome these problems is to introduce inclusive education, which aims to provide equal access to education for all students, including children with special needs. With the principle of justice and respect for the form of human diversity, the relationship between inclusive education and the Qur'an is very related. This study aims to examine inclusive education from the Qur'anic perspective in building social equality. Through the method of literature review, this research attempts to analyze relevant Qur'anic verses and relate them to the concept of inclusive education. By examining the QS. Al-Hujurat verse 13 and QS. Ar-Rum verse 22, it is known that the Qur'an emphasizes the importance of knowing and respecting differences in fellow human beings. This is in line with inclusive education, which is committed to providing equal access to all students and emphasizes the importance of fair and non-discriminatory treatment. Moderate attitudes, as part of social equality, enable the creation of an inclusive educational environment where all students can learn and develop without pressure or discrimination. The results of this study are expected to contribute to the creation of practical guidelines for educators and policy makers, as well as to change people's perceptions of diversity and inclusion. Ultimately, this research aims to support the creation of a more harmonious and equitable society and build a more inclusive social structure.